2009
DOI: 10.1007/s00125-009-1537-y
|View full text |Cite
|
Sign up to set email alerts
|

Regression of diabetic complications by islet transplantation in the rat

Abstract: Aims/hypothesis Type 1 diabetes is a chronic disease leading to complications such as peripheral neuropathies, nephropathy and cardiovascular disease. Pancreatic islet transplantation is being extensively investigated for blood glucose control in animals and in human type 1 diabetic patients, but the question of whether it can reverse long-term diabetic complications has not been fully explored. We investigated the effects of islet transplantation on diabetic complications in a rat model of streptozotocin-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Animal studies and clinical phase I/II trials in patients with T1D who take C-peptide as replacement therapy provide direct evidence of a protective effect of C-peptide against diabetes-induced complications of the kidneys, the peripheral nerves, and CNS function [18][19][20]. In addition, it has been shown that T1D patients with residual beta cell function or receiving whole pancreas or allogeneic islet transplantation do not develop long-term complications, a result that could be attributed to a positive effect of C-peptide [21][22][23][24][25]. These results identify C-peptide as a compelling novel therapeutic candidate in T1D.…”
Section: Introductionmentioning
confidence: 94%
“…Animal studies and clinical phase I/II trials in patients with T1D who take C-peptide as replacement therapy provide direct evidence of a protective effect of C-peptide against diabetes-induced complications of the kidneys, the peripheral nerves, and CNS function [18][19][20]. In addition, it has been shown that T1D patients with residual beta cell function or receiving whole pancreas or allogeneic islet transplantation do not develop long-term complications, a result that could be attributed to a positive effect of C-peptide [21][22][23][24][25]. These results identify C-peptide as a compelling novel therapeutic candidate in T1D.…”
Section: Introductionmentioning
confidence: 94%
“…Figliuzzi et al (11) 16000 IS+: 18 ± 8 IS-: 7.5 ± 0.2 Yun Lee et al (63) 1200 >365 Remuzzi A et al (39) 3000 80 O'Sullivan et al (36) …”
Section: -70mentioning
confidence: 99%
“…Various independent investigators have shown that in diabetic patients there is extensive impairment in left ventricular functions before the clinical signs of congestive heart failure become manifest. Diastolic dysfunction has been defined as the earliest sign of diabetic myocardial disease to occur before systolic impairment [2,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The term diabetic cardiomyopathy (DCM) refers to heart disease caused by diabetes. DM is asymptomatic in the early stages and it is associated with a poor prognosis and irreversible changes [2]. Although there are many studies conducted in adult patients, there are a very limited number of studies in children and adolescents in the literature.…”
Section: Introductionmentioning
confidence: 99%